2020
DOI: 10.3889/oamjms.2020.5502
|View full text |Cite
|
Sign up to set email alerts
|

Worden’s Task-Based Model for Treating Persistent Complex Bereavement Disorder During the Coronavirus Disease-19 Pandemic: A Narrative Review

Abstract: BACKGROUND: A wide range of studies has shown that the coronavirus disease (COVID)-2019 pandemic could cause many deaths on the global scale by the end of 2020 because of the high speed of transmission and predicted case-fatality rates. AIM: This paper is a narrative review aiming to address the treatment of persistent complex bereavement disorder (PCBD) during the COVID-19 crisis using Worden’s task-based model. MATERIALS AND METHODS: Related papers published from 2000 to 2020 were searched in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Health care workers who were isolated or working in high-risk locations had 2-3 times higher risk of posttraumatic stress [8]. There are many reasons behind mental health problems such as increasing number of confirmed and suspected cases, overwork, decline of personal protective equipment, widespread media coverage, lack of certain drugs, fear of infection for themselves and their families, caring for severing ill patients, caring for colleagues who have also become ill, and multiple losses [9], [10], [11], [12]. Hence, psychological support among health care workers is a critical part of the public health response.…”
Section: Introductionmentioning
confidence: 99%
“…Health care workers who were isolated or working in high-risk locations had 2-3 times higher risk of posttraumatic stress [8]. There are many reasons behind mental health problems such as increasing number of confirmed and suspected cases, overwork, decline of personal protective equipment, widespread media coverage, lack of certain drugs, fear of infection for themselves and their families, caring for severing ill patients, caring for colleagues who have also become ill, and multiple losses [9], [10], [11], [12]. Hence, psychological support among health care workers is a critical part of the public health response.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, women are often targets of verbal and physical violence, especially in patriarchal countries. Other risk groups who may develop or progress mental illness include people with pre-existing mental health problems, survivors of domestic violence, survivors experiencing multiple losses [34], [35], people in lower-income households, loners, and socially excluded populations, such as prisoners, refugees, etc. [36].…”
Section: Discussionmentioning
confidence: 99%
“…Ill-prepared media reports can fuel panic and increase the suicide rate [34]. According to some reports, the suicide statistics may increase by 13% after non-adequate media messages [41].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the available evidence has revealed that stressful jobs are more likely to cause occupational burnout. In major pandemics, including COVID-19, healthcare providers and professionals often experience higher than average workloads, longer shifts, strict organizational regulations, less time to cope with occupational hazards, sleep deprivation, disruptions of work-life balance, limited supportive resources, and grief caused by multiple losses [1], [2], [3]. These challenges often lead to emotional exhaustion, as feelings of physical and mental depletion caused by the work environment.…”
Section: To the Editormentioning
confidence: 99%